Penggunaan Storytelling sebagai Media Kreatif dalam Pembelajaran Teks Recount di SMK Negeri 5 Pekanbaru - Putri Nadhira; Chika Rahmadany; Fauzan Azim (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Storytelling is an effective learning method in teaching recount text because it can improve students' language skills. This study aims to analyze the effectiveness of using storytelling as a creative media in learning recount text at SMK Negeri 5 Pekanbaru. The method used in this study is a literature study by analyzing various journals as the main source of data. The results of the study indicate that storytelling contributes positively to improving students' understanding of the structure and content of recount texts. In addition, this method helps enrich students' vocabulary and improve their speaking and writing skills in English. Thus, storytelling can be used as an innovative alternative in teaching recount texts to create more interesting and interactive learning. The implication of this study is the need to develop more varied storytelling strategies so that learning outcomes are more optimal.